Circulating microRNAs as predictors of cardiovascular disease—more than a miRage? - Gidlöf, Olof (Journal of Laboratory and Precision Medicine, 2017)
Coronary artery disease (CAD) is a leading cause of morbidity and mortality globally, and reliable prognostic tools for identifying subjects at risk of developing a cardiovascular event is currently a great unmet clinical need (1). Despite the considerable effort that has been put into developing risk prediction model, the accuracy of traditional risk factors is insufficient for predicting cardiovascular events in a substantial proportion of patients.